EGO SINTONIK TOKOH-TOKOH HOMOSEKSUAL DALAM NOVEL INDONESIA MODERN - Iswadi Bahardur (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2014)
Various human behavior in life is the result of conflict and reconciliation of aspects of personality called the id, ego, and superego. Unbalance function of these aspects will result in the emergence of deviant behavior. The uncontrolled aspect of ego causes people do not able to consider the feasibility of actions in terms of moral values, tends behalf of self pleasure without measure the value of good and bad. Homosexual behavior is one of theexamples of deviant behavior in human is caused by uncontrolled ego aspect by another aspect of personalities.One of the phenomenon in modern Indonesian novels is rampant homosexual themes which also being warmly discussed in various countries in the world now. In reality, few countries in the world even has legalized homosexual marriage. The emergence of homosexual themes in reality imaginative novels of modern Indonesian literature indicates that it reflects the problems that raged in the community in which the work was created.This study aimed to describe the human syntonic ego problem with homosexual behavior, especially the characters contained in the novels of modern Indonesia. The results showed that homosexual characters, gay (homosexual designation for men) and lesbian (homosexual designation for women) in the novels that became the source of the data has syntonic ego. The sexual orientation of these characters are deviate, like the same sex. The characters are comfortable with their sexual orientation, not in conflict with himself, and not trying to change their sexual orientation to be normal.